Early Signs of Autism and It’s Relation with Gestational Factors: An Urban Based Study in Bangladesh - Sharmin, Saida; Halim, Kazi Shafiqul; Sultan, Zobayed; Haque, Kazi Mahbubul (Bangladesh Medical Journal, 2022)
A cross-sectional study was conducted to observe the prevalence autism spectrum disorders (ASD) and its correlation with gestational factors in country population between January and December of 2016. The study population was nursery school child aged 3-5 years whose parents were willing to participate in the study. In this study, the children are excluded whom already being identified as any forms of autism spectrum disorders. Convenient sampling technique was followed to select the samples from 47 schools of Uttara, Ashulia and Nikunjo area of Dhaka City Corporation and Tongi area of Gazipur City Corporation under Dhaka Division, Bangladesh. A total of 1000 children were recruited in the study. The research instrument was a semi-structured questionnaire based on Early Screening of Autistic Traits (ESAT) tool. Based on the diagnosis of the cases, parents were invited to another interview to fill out questionnaire related to some parental and gestational factors to assess the relationship with autism. The study found early signs of autism in 2.6% cases (26 in 1000), by using Early Screening of Autistic Traits (ESAT) questionnaire. Among the children having early signs of autism, history of normal birth weight was found more in term pregnancy (62.5%) than its preterm counterpart (60.0%). Growth parameter was higher in normal birth weight (68.8%) than low birth weight (60.0%). Similarly, growth parameter was also higher in children that are from 3rd gravida (75.0%) than that of 2nd gravida (66.7%) and 1st gravida (61.5%). Birth weight was also higher in >2 years birth spacing (60.0%) than that of <2 years (50.0%). Complication was more in home delivery (50.0%) than institutional delivery (20.8%). Birth injury happened more in home delivery than institutional delivery. Similarly, complication during delivery was higher in >2 years birth spacing (30.0%) than that of <2 years (0%), However, the difference was not significant statistically in any of the comparisons (P>0.05). Hence, no causal relation was found between autism and gestational factors. Bangladesh Med J. 2021 May; 50(2) : 9-14